The use of intravenous immunoglobulin in dengue shock syndrome a randomized double blind placebo controlled trial - Frias, Melchor Victor G.
To determine the efficacy of intravenous immunoglobulin (IVIG) in affecting the outcome of pediatric patients with Dengue Shock Syndrome (DSS). Randomized double-blind placebo controlled trial at De La Salle University Medical Center, Dasmari?as, Cavite.Two hundred five consecutive patients aged six months to fourteen years with Dengue Hemorrhagic Fever (DHF) grade III or IV (WHO Classification) based on the World Health Organization (WHO) Clinical and Laboratory criteria and and confirmed by Enzyme-linked immunosorbent assay (ELISA).Eligible patients were randomly assigned to either of two groups: control or experimental group. The control group received placebo while the experimental group received IVIG at 0.4 g/kg, once a day for 3 days.Mortality was the main outcome measure. Morbidities such as progression of severity, complications and adverse events were also considered as primary outcomes. Secondary outcomes include duration of rise of platelet count, duration of shock and duration of hospital stay.The crude relative risk was estimated at 95 confidence level. Considering the effects of confounders, the adjusted relative risk was also estimated at a 95 confidence level using the multiple logistic regression analysis. Aside from this estimation approach of data analysis, the null hypothesis that the mortality rate of the two treatment groups are equal was tested using the chi-square test at a=0.05. The nature and frequency of the adverse reactions were noted and the incidence of adverse events were compared for the two groups using the chi-square test at a=0.05. The relative risk of adverse reactions was also estimated at a 95 confidence level.A total of 216 patients were recruited and randomized into two treatment groups. Eleven patients were unconfirmed DHF cases. Thus, 205 patients were included, 103 were given IVIG and 102 were given placebo. Overall mortality rate (MR) was 21. The mortality rate in those given IVIG and placebo was 15 and 28 respectively. There was a trend of reduction in mortality among those given IVIG with RR of 0.51, CI of 0.29, 0.90. DSS grade 3 patients given IVIG were half less likely to deteriorate or progress to grade 4 with a relative risk (RR) of 0.46 and 95 confidence interval (CI) of 0.23, 0.91. Cardiac involvement was the most common complication (12) but there was no significant difference in complication rate between the two groups (RR of 0.65, CI of 0.36, 1.20). In terms of adverse events, patients given IVIG had a RR of 1.6 with CI of 0.95, 2.68. The most common adverse event was rash. Patients given IVIG had an earlier rise in platelet count and earlier recovery from shock. There was no difference in the duration of hospitalization between the two groups. Intention to treat analysis still revealed a trend in the reduction of mortality (RR of 0.58, CI of 0.35, 0.97). Absolute risk reduction (ARR) was 0.12 (CI of 0.01, 0.23) and the number needed to treat (NNT) was 8 (CI of 4.33, 101.75).Administration of IVIG in pediatric patients with DSS may be safe and beneficial as it may reduce the risk of mortality.
Thesis (Master of Science in Epidemiology)--University of the Philippines Manila.
Keywords: Immunoglobulins